ANALISA INDEKS KUALITAS INFRASTRUKTUR DRAINASE PERKOTAAN DAN JARINGAN IRIGASI DI KABUPATEN SIKKA - Bhara, Firnimus Konstantinus; Lete, Maria Kurniaty (Journal of Science and Engineering, 2024)
At the end of December 2023, there was a problem of surface runoff or runoff at several locations in Sikka Regency. The impact of this runoff caused traffic flow activities to become congested due to sedimentation in the form of plastic, wood, and rubbish from the drainage towards the road; and in February 2024 there a problem of thousands of toddlers in Sikka Regency experiencing stunting/malnutrition. These two problems raise a question about the quality of drainage channels and irrigation channels in Sikka district, whether they function optimally in minimizing urban runoff for urban drainage, and can channel water flow to tertiary plots to irrigate rice fields for the irrigation network system. ?; this research aims to provide information to readers regarding the quality assessment of the physical infrastructure of urban drainage infrastructure and existing irrigation networks based on Ministerial Regulation Number 12/PRT/2015. The method used in this research is a case study or field study method, at 5 research locations, namely urban drainage in the districts of Kota Uneng, Kabor, and Beru as well as the Koro Irrigation Network in Magepanda District and the Kojablo Irrigation Network in Talibura District; Next, the data is processed and analyzed using Excel 2019 software and conclusions are drawn. The research results show that the percentage for urban drainage is 31%, categorized as severely damaged drainage conditions; while the percentage of the irrigation network was 58.50%, which was categorized as the condition of the irrigation network being moderately damaged.